Eddie Elejar a ballet pedagogue of hi time - Revilla, Jantu Paula M. (2012.)
This study has been organized as a qualitative biographical study in an effort to explore connections that Elejar developed with several company members during their years with Manila Metropolis Ballet. This study made use of qualitative research rather than quantitative because of the techniques employed by the researcher. Data was descriptive making use of field notes and interview transcripts. Here, reports are descriptive and conceptual. Structures interviews were conducted with Elejar. The researcher proceeded with the initial private interview conducted with Elejar. The significant names and dates were narrated as he unfolded information towards his early involvement with three historical home grown dance companies. He also mentioned several turn events with signifanct calendar dates for more background. Soon afterwards, he mentioned names of influential people in dance such as Felicitas Layag-Radaic, Julie Borromeo, and Antonio Fabella.
Keywords: Ballet dancers